PENGARUH KELENGKAPAN PRODUK DAN STORE ATMOSPHERE TERHADAP KEPUTUSAN PEMBELIAN UD.ARYAWAN DENPASAR SELATAN - Suryawan, Tjokorda Gde Agung Wijaya Kesuma; Cahyani, Ni Made Yuli; Mandiyasa, I Kadek Sara (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2023)
The development of the retail business in Indonesia which is growing rapidly makes competition increase. As a form of retail business, UD. Aryawan who is in, South Denpasar must have an advantage over competitors in order to survive or even win the competition in the retail business. One way to create a competitive advantage is to apply the right marketing mix so that it can satisfy consumers. This study aims to determine the effect of Product Completeness and Store Atmosphere on Consumer Purchase Decisions at UD. Aryawan South Denpasar, as well as knowing which factors have a dominant influence on consumer purchasing decisions at UD. Aryawan South Denpasar. Sampling was carried out using Accidental Sampling as many as 97 respondents. Data collection methods used are observation, interviews, literature study and questionnaires (questionnaire). The data analysis technique used is quantitative analysis consisting of validity test, reliability test, classical assumption test, multiple linear regression analysis, analysis of determination, statistical analysis of F test (F-test) and statistical analysis of t-test (t-test). The results showed that there was a positive and significant effect simultaneously and partially between product completeness and Store Atmosphere on purchasing decisions at UD. Aryawan, South Denpasar.